Disrupted circadian expression of β-arrestin 2 affects reward-related µ-opioid receptor function in alcohol dependence - Meinhardt, Marcus W.; Giannone, Francesco; Hirth, Nathalie; Bartsch, Dusan; Spampinato, Santi M.; Kelsch, Wolfgang; Spanagel, Rainer; Sommer, Wolfgang H.; Hansson, Anita C. (Journal of neurochemistry, 2022)
There is increasing evidence for a daily rhythm of µ-opioid receptor (MOR) efficacy and the development of alcohol dependence. Previous studies show that β-arrestin 2 (bArr2) has an impact on alcohol intake, at least partially mediated via modulation of MOR signaling, which in turn mediates the alcohol rewarding effects. Considering the interplay of circadian rhythms on MOR and alcohol dependence, we aimed to investigate bArr2 in alcohol dependence at different time points of the day/light cycle on the level of bArr2 mRNA (in situ hybridization), MOR availability (receptor autoradiography), and MOR signaling (Damgo-stimulated G-protein coupling) in the nucleus accumbens of alcohol-dependent and non-dependent Wistar rats. Using a microarray data set we found that bArr2, but not bArr1, shows a diurnal transcription pattern in the accumbens of naïve rats with higher expression levels during the active cycle. In 3-week abstinent rats, bArr2 is up-regulated in the accumbens at the beginning of the active cycle (ZT15), whereas no differences were found at the beginning of the inactive cycle (ZT3) compared with controls. This effect was accompanied by a specific down-regulation of MOR binding in the active cycle. Additionally, we detect a higher receptor coupling during the inactive cycle compared with the active cycle in alcohol-dependent animals. Together, we report daily rhythmicity for bArr2 expression linked to an inverse pattern of MOR, suggesting an involvement for bArr2 on circadian regulation of G-protein coupled receptors in alcohol dependence. The presented data may have implications for the development of novel bArr2-related treatment targets for alcoholism.